Ability of ultrasound imaging to detect erosions in a bone phantom model. Issue 9 (19th July 2010) - Koski, Juhani M; Alasaarela, Eeva; Soini, Irma; Kemppainen, Kari; Hakulinen, Ullamari; Heikkinen, Jari O; Laasanen, Mikko S; Saarakkala, Simo
Abstract : Objectives: The authors examined the validity, interobserver reliability and interscanner variation in detecting bone erosions with ultrasonography using a custom-made phantom. Methods: 21 bovine bones were used. Artificial erosions were made into 15 bones and six bones were left as controls. In the processed bones the numbers of erosions, their depths and widths varied between 1–7, 1–4 and 1.5–5 mm, respectively. Each bone was coated with polyvinyl alcohol cryogel to mimic overlying soft tissue and to hide the erosions. Four musculoskeletal sonography experts scanned the 21 blind-coded phantoms using one of the three sets of ultrasound equipment. Finally, quality assurance measurements of the ultrasound equipment was carried out using two additional bone samples. Results: The sonographers detected the erosions successfully with ultrasound. The mean correlation coefficient for a correct result in terms of the number of erosions detected was 0.88 (range 0.75–0.975). The overall Cohen's κ coefficient for interobserver agreement was 0.683 in terms of discrimination between healthy bones and bones with erosions. The different sets of equipment showed that their overall performance was equal. Conclusions: The sonographers had good correlations with the number of erosions and they were successful in separating healthy bones from bones with erosions. It seems that neither depth nor width is crucial but that in experimental conditions a 1.5 mm erosion width was the limit for the resolution with current ultrasound equipment. Ultrasound is a valid and reliable method of detecting cortical bone erosions in vitro, when the round erosion is at least 1 mm deep and 1.5 mm wide.